Adverse events associated with donor plateletpheresis: A 10-year experience from Vojvodina, Serbia - Budakov Obradović, Zorana; Bujandrić, Nevenka; Grujić, Jasmina (Vojnosanitetski pregled, 2022)
Background/Aim. Plateletpheresis (PLTP) is a medical procedure used for collecting donor platelets with multiple benefits for patients who will receive apheresis platelets. The procedure takes one hour and is well tolerated by donors. Nevertheless, adverse events (AEs) may occur during and after the PLTP procedure. The aim of the study was to determine the incidence and type of AEs associated with PLTP in donors. Methods. A retrospective analysis of AEs associated with donor PLTP was conducted at the Blood Transfusion Institute of Vojvodina from January 1, 2010, to December 31, 2019. Results. Out of 2,073 platelet donors, 94.84% were multiple blood donors, predominantly male (98.55%). AEs were identified during 180 (8.68%) platelet donations with no statistical significance in occurrence in the first time donors (10.28%) and repeat donors (8.59%). Mild local reactions related to venous access (42.22%) were the most common AEs. Generalized symptoms were exhibited in 16.67% of donors, 26.11% exhibited symptoms related to apheresis (citrate reactions), and 15% exhibited those related to other complications. It was found that 95.55% of AEs occurred during PLTP and only 4.45% after it. Conclusion. Donor PLTP is a generally safe procedure, well tolerated by donors. Understanding risk factors for a possible occurrence of AEs provides support for adopting measures to prevent them.
Keywords: blood donors; drug-related side effects and adverse reactions; plateletpheresis; risk factors.